2017
DOI: 10.1111/iwj.12720
|View full text |Cite
|
Sign up to set email alerts
|

A new option for definitive burn wound closure – pair matching type of retrospective case–control study of hand burns in the hospitalised patients group in the Dr Stanislaw Sakiel Centre for Burn Treatment between 2009 and 2015

Abstract: Nearly 80% of all burns include the hands of affected individuals. Skin grafting is the gold standard in burns treatment, but in the case of the burn wound bed, it may require the necessity of utilising skin substitutes to facilitate closure. The aim of this study is to assess the impact of a porcine-derived wound dressing (Oasis™) for application to hand burns compared to a synthetic dressing (Suprathel™). Comparative assessments were made, including the time to heal, quality of healing and pain intensity. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The optimal method of treatment for extensive full‐thickness skin burns (III°) is to perform an autologous split‐thickness skin graft (STSG) donated from a body part with intact skin (Busuioc et al, ; Glik et al, ; Grossova, Zajicek, Kubok, & Smula, ; Kitala et al, ; Prim et al, ). However, despite total tissue compliance, which should be considered the main advantage of STSG, such grafts have a number of disadvantages and limitations (Kitala et al, ; Table , Figure a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal method of treatment for extensive full‐thickness skin burns (III°) is to perform an autologous split‐thickness skin graft (STSG) donated from a body part with intact skin (Busuioc et al, ; Glik et al, ; Grossova, Zajicek, Kubok, & Smula, ; Kitala et al, ; Prim et al, ). However, despite total tissue compliance, which should be considered the main advantage of STSG, such grafts have a number of disadvantages and limitations (Kitala et al, ; Table , Figure a).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite total tissue compliance, which should be considered the main advantage of STSG, such grafts have a number of disadvantages and limitations (Kitala et al, ; Table , Figure a). In order to overcome these limitations, the application of biological skin substitutes may be considered (Glik et al, ; Kitala et al, ), the advantage of which may be, for example, the reduction of the donor site surface area and shortening the time of hospitalization of burn patients (Kitala et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wong–Baker and Comfort B scores used by Glat et al [ 7 ] and Rashaan et al [ 16 ] showed values between no pain and minimal pain after ST treatment. Glik et al [ 8 ] showed OASIS superior only on day four without statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Burn severity might also influence hospital LOS, which could not be considered due to insufficient data. In prospective ST and PX studies, hospital LOS ranged from 0 [ 5 ] to 23.3 days [ 9 ] and 2 to approximately 40 days [ 8 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation